Novel Energetic Co-Reactant for Thermal Oxide Atomic Layer Deposition: The Impact of Plasma-Activated Water on Al2O3 Film Growth - Chaves, João; Chiappim, William [UNESP]; Karnopp, Júlia; Neto, Benedito; Leite, Douglas; da Silva Sobrinho, Argemiro; Pessoa, Rodrigo (MDPI, 2023)
In the presented study, a novel approach for thermal atomic layer deposition (ALD) of Al2O3 thin films using plasma-activated water (PAW) as a co-reactant, replacing traditionally employed deionized (DI) water, is introduced. Utilizing ex situ PAW achieves up to a 16.4% increase in the growth per cycle (GPC) of Al2O3 films, consistent with results from plasma-enhanced atomic layer deposition (PEALD). Time-resolved mass spectrometry (TRMS) revealed disparities in CH4 partial pressures between TMA reactions with DI water and PAW, with PAW demonstrating enhanced reactivity. Reactive oxygen species (ROS), namely H2O2 and O3, are posited to activate Si(100) substrate sites, thereby improving GPC and film quality. Specifically, Al2O3 films grown with PAW pH = 3.1 displayed optimal stoichiometry, reduced carbon content, and an expanded bandgap. This study thus establishes “PAW-ALD” as a descriptor for this ALD variation and highlights the significance of comprehensive assessments of PAW in ALD processes.
Keywords: alumina; atomic layer deposition; growth per cycle; plasma-activated water